Locoregional Tumor Therapy - Van Cutsem, Eric.; Van Cutsem, Eric.; Vogl, Thomas J.; Vogl, Thomas J.; Orsi, Franco.; Orsi, Franco.; Sobrero, Alberto.; Sobrero, Alberto. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
Recent years have witnessed a renaissance in the use of locoregional tumor therapy as part of a multimodal therapeutic approach to a variety of solid tumors, and attempts are underway to define its value in the overall therapeutic strategy for individual tumor entities. This flourishing of interest in locoregional tumor therapy derives from a series of important new developments concerning methodology, drug treatments, and instrumentation. The resulting approaches include not only optimized locoregional chemotherapy and chemoembolization for hepatocellular carcinoma and other tumors, but also other “targeted” therapies such as stereotactic radiosurgery, radiofrequency ablation, intra-arterial administration of radiopharmaceuticals, and complex new methods of chemoembolization of liver metastases involving the use of multiagent chemotherapy in combination with targeted drugs, drug-eluting beads/microspheres, or nanoparticles. In addition, intraperitoneal and intrapleural therapies, e.g., cytoreduction plus hyperthermic intraperitoneal chemotherapy, are now a standard element of the strategy for a range of tumors. It is vital that practitioners have the necessary expertise in the use of these locoregional treatment methods and understand how to combine them optimally with modern systemic therapies. With that goal in mind, this book presents, in condensed form, the clinical results achieved using various locoregional tumor therapies. In so doing, it will allow the reader to rapidly retrieve the information on indications and effectiveness that is required for optimal integration of these highly effective therapies into modern, yet more complex treatment strategies.